The Influence of Teamwork and Communication on Employee Performance at Phenom Event Indonesia in Bali - Harahap, Poppy Raudah; Berutu, Edi Putra (Journal of Economics and Social Sciences (JESS), 2025)
This research aims to determine the impact of team collaboration and communication on employee performance at Phenom Event Indonesia in Bali. The population and sample in this study consist of 70 employees using a saturated sample technique. Data collection techniques include observation and distribution of questionnaires. This research employs a quantitative research method with a descriptive type of study, encompassing validity tests, reliability tests, classical assumption tests, hypothesis tests (t-test, F-test, and analysis of determination coefficient (R2) test). The research results from the determination coefficient (R2) test indicate that the variables of teamwork and communication influence employee performance by 59.7%, while the remaining 40.3% is influenced by other variables not examined in this study.